2004
DOI: 10.1161/01.hyp.0000111139.94378.74
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelin-1 in Blood Pressure Regulation in a Rat Model of Visceral Obesity and Hypertension

Abstract: Abstract-Endothelial dysfunction has been suggested to play an important role in the development of obesity-induced hypertension. Because endothelin release increases in response to endothelial damage, we examined whether endothelin-1 contributes to increased arterial pressure in a model of visceral obesity produced by feeding SpragueDawley rats a high-fat (HF) diet (40% fat w/w, nϭ6) for 12 months. Arterial and venous catheters were implanted for measurement of mean arterial pressure (MAP) and heart rate (HR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
4
22
0
3
Order By: Relevance
“…This indicates a selective enhancement of ET A receptor-dependent vasoconstrictor tone in obese hypertensive patients. 43 In contrast, da Silva et al 44 found that long-term blockade of ET A receptors reduced arterial pressure similarly in a rat model of visceral obesity and in control normotensive animals, suggesting that endothelin-1 does not contribute to the elevation of arterial pressure in this model of central obesity. These data may also indicate that endothelin antagonism alone is not sufficient to restore the impaired NO bioavailability in obesity.…”
Section: Vascular Alterationsmentioning
confidence: 84%
“…This indicates a selective enhancement of ET A receptor-dependent vasoconstrictor tone in obese hypertensive patients. 43 In contrast, da Silva et al 44 found that long-term blockade of ET A receptors reduced arterial pressure similarly in a rat model of visceral obesity and in control normotensive animals, suggesting that endothelin-1 does not contribute to the elevation of arterial pressure in this model of central obesity. These data may also indicate that endothelin antagonism alone is not sufficient to restore the impaired NO bioavailability in obesity.…”
Section: Vascular Alterationsmentioning
confidence: 84%
“…Overweight and obese humans have enhanced ET-1-mediated endothelial dysfunction (194). An ET A receptor antagonist attenuated HFD-induced hypertension in rats having increased visceral obesity and leptin levels (34). Indirect evident suggests that this pathway is augmented in obese preeclamptic situations.…”
Section: Effects Of Obesity On Placental Ischemia-induced Endothelialmentioning
confidence: 99%
“…However, the mechanisms whereby obesity causes hypertension are not fully understood. To better understand those mechanisms, different investigators have used a rat model fed an HF diet (2,4,33). We have chosen this model because it mimics the effects of human HF-food consumption; rats develop characteristic features of human obesity-induced hypertension, including increased renal tubular reabsorption and glomerular filtration rate (GFR) (8).…”
mentioning
confidence: 99%